PEMANFAATAN SENSOR ULTRASONIC BERBASIS ATMEGA16 PADA PORTAL OTOMATIS - Mohammad Noviansyah; Hafdiarsya Saiyar (Jurnal Akrab Juara, 2018)
In an increasingly technological developments rapidly, the use of a tool that can help the human work easier. The use of sensors that are then processed by a microcontroller making a tool can be used to become a tool in everyday human activities. The use of ultrasonic sensor-based microcontroller atmega16 can serve as a reader about a situation in front of him. The utilization of these tools can be applied in the opening a portal or haling the door automatically, which will read the existence of an object at a specified place and distance. Sensor used the opening of the Portal will automatically read the existence of an obstacle in front, so that by the time the sensor is reading the existence of impediments at the spot that has been determined, then the portal will automatically open. As is otherwise when the object is not located on the area of the Hall, then the Portal will close by itself. Keywords:microcontroller, ultrasonic,atmega16.